SemKnow: A semantic knowledge management system for scholarly repositories - Ugochi Isika, N.; Ismail, M.A. (2012)
Knowledge sharing (KS) is an important component of knowledge management. Through KS, the creation and dissemination of new knowledge is made possible. The authors propose SemKnow semantic knowledge management system to enhance the functionality of scholarly repositories. Repositories are commonly used by academic institutions to manage the research work of their scholars and enhance visibility among peers. Previous research done by the authors was used to identify the factors influencing knowledge sharing among postgraduate student at one of the research intensive university in Malaysia. This paper proposes a KMS tool for enhancing knowledge sharing using the semantic web.